The Implementation Of The Community Based Tourism Concept In Cultural Heritage Management As A Tourist Attraction In Batuan Village Temple Gianyar Bali - Wiwin, I Wayan (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2019)
Community-based tourism is the concept of tourism development by prioritizing the active participation of the community with the aim of providing welfare for them while maintaining environmental quality, and protecting their social and cultural life. One of the legacies of Bali's cultural heritage which is also used as a tourist attraction is Batuan Village Temple which is located in Batuan Village, Sukawati District, Gianyar Regency, Bali. This study examines three problems, namely: (1) How is the application of the concept of community-based tourism in managing cultural heritage as a tourist attraction in Batuan Temple?; (2) What factors support the application of the concept of community based tourism in the management of cultural heritage as a tourist attraction in Batuan Village Temple?; and (3) What is the model of community based tourism in cultural heritage management as a tourist attraction in Batuan Village Temple?. This research is a qualitative research method of collecting data through observation, interviews, and documentation. Informants in this study were selected by purposive sampling method. Data analysis was carried out descriptively, qualitatively, and interpretatively. The results showed that the management of cultural heritage of  Batuan Village Temple as a tourist attraction has applied the four principles of community based tourism, those are; the principle of community participation; principles of nature conservation; the principle of the local economy; and socio-cultural conservation principles. The factors that support the application of the concept of community based tourism in Batuan Village include: tourism potential owned by Batuan Village, the aspirations of the villagers of Batuan Village, the synergy among tourism stakeholders in Batuan Village, the support of the Gianyar Regency Government, and social capital owned by villagers of Batuan Village. The management model of Batuan Temple as a pure tourist attraction is managed by the villagers of Batuan Village by applying the principles of community-based tourism in order to achieve common expectations, namely the welfare of the residents of Batuan Village and to realize the sustainable tourism development.